Urban stream assessment system (UsAs): An integrative tool to assess biodiversity, ecosystem functions and services - Elina Ranta (Elsevier, 2021)
Urban streams and ecosystems are highly affected by the intense development of cities and an increase of impervious surfaces. If these environments are close to their pristine state, they can be considered a nature-based solution promoting the integration of both green and blue elements in the cities, while providing a wide range of services (e.g. better aesthetics, air quality, leisure areas, and mitigation of climatic changes). In view of this, the current study aimed to develop a holistic assessment tool for urban streams that can be used to highlight their importance and support decision makers in the elaboration of measures to recover urban streams. The tool called Urban stream Assessment system (UsAs) includes the assessment of (1) biodiversity, (2) ecological functions and habitat that are inherent components of the ecosystems, and (3) provisioning, regulating, and cultural services, following The Millennium Ecosystem Assessment (MA) and the Common International Classification of Ecosystem Services (CICES). The tool includes 89 indicators belonging to 17 divisions (services and functions) selected from studies on urban areas and fluvial ecosystems. In addition, the tool introduces a method for the measurement of an indicator, rationale for the used indicator, positive and negative scope of the indicator, and reference to the proposed method. The tool incorporates also a step-by-step scoring system, which results in a global quality classification of streams. The UsAs tool was tested with a case study stream located in the city of Coimbra, Central Portugal. The final classification attributed to this stream was moderate, which is slightly higher than the ecological status, highlighting its potential ecosystem services (ES). However, the UsAs clearly showed a poor biodiversity (namely of aquatic invertebrates, amphibians, fish, aquatic mammals, and terrestrial insects), habitat conditions and the most compromised services that could be improved: water supply, air quality, health and well-being. The use of this novel tool supports also new research and knowledge on aquatic ecosystems and particularly urban streams by generating relevant data to answer and test important ecological questions, such as the influence of biodiversity in ecosystem functioning and services. Further investigation should focus more on tests in different types of urban streams, regions, and climates.